2001
DOI: 10.1200/jco.2001.19.22.4202
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Radiation Dose Escalation With Concurrent Weekly Full-Dose Gemcitabine in Patients With Advanced Pancreatic Cancer

Abstract: The final dose investigated (42 Gy) is not recommended for further study considering the occurrence of both acute and late toxicity. However, a phase II trial of this novel gemcitabine-based chemoradiotherapy approach, at a radiation dose of 36 Gy in 2.4-Gy fractions, is recommended on the basis of tolerance, patterns of failure, and survival data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
159
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(169 citation statements)
references
References 17 publications
7
159
0
3
Order By: Relevance
“…Although we found no consensus between administration schedules for gemcitabine with radiation, recent studies have used twice weekly or weekly administrations of gemcitabine for their main therapeutic schedules (Blackstock et al, 1999;McGinn et al, 2001;Okusaka et al, 2004;Magnino et al, 2005). According to the fact that patients with resectable pancreatic cancer developed early recurrence after surgery due to micrometastases and distant early metastases were important cause of treatment failure of chemoradiotherapy in patients with locally advanced pancreatic cancer, we used weekly gemcitabine treatments in our study (Yeo et al, 1997;Paulino and Latona, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we found no consensus between administration schedules for gemcitabine with radiation, recent studies have used twice weekly or weekly administrations of gemcitabine for their main therapeutic schedules (Blackstock et al, 1999;McGinn et al, 2001;Okusaka et al, 2004;Magnino et al, 2005). According to the fact that patients with resectable pancreatic cancer developed early recurrence after surgery due to micrometastases and distant early metastases were important cause of treatment failure of chemoradiotherapy in patients with locally advanced pancreatic cancer, we used weekly gemcitabine treatments in our study (Yeo et al, 1997;Paulino and Latona, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used a full dose of gemcitabine (1000 mg m À2 ) to maximise systemic cytotoxicity. Although most of the recent phases I and II studies were performed using a submaximal dose of gemcitabine with radiotherapy, a study by McGinn et al (2001) reported that the standard full dose of gemcitabine was acceptable. Our previous experience also showed that radiotherapy with a full dose of gemcitabine was tolerable (Chung et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, since the gemcitabine group has a beneficial effect on survival rate compared with the fluorouracil group, gemcitabine is the drug of choice for progressive pancreatic cancer at present. However, in recent findings, there is a significant toxic effect of gemcitabine combined with radiation in the treatment of advanced pancreatic cancer (McGinn et al, 2001(McGinn et al, , 2002Wolff et al, 2001;Crane et al, 2002). In addition, since existing antipancreatic cancer drugs have no eradicative potency, it is necessary to find medicines that have new mechanisms of antitumour activity.…”
mentioning
confidence: 99%